Social Media Strategies in Product-Harm Crises - He, Shu; Rui, Huaxia; Whinston, Andrew B. (Information Systems Research, 2018)
When a focal firm undergoes a product-harm crisis, nonfocal firms offering similar products or services can suffer from a negative spillover effect, but can also benefit from customers switching from the troubled focal firm, which we call the competitive effect. In response, a nonfocal firm can adapt its marketing strategy in consideration of these two opposing effects. Because social media is a flexible medium through which firms can quickly adjust marketing strategies in response to such unexpected events, we study how nonfocal firms adjust their post-crisis social media efforts to induce purchases and to improve customer relationships—two strategies known in the literature as offensive and defensive marketing, respectively. In particular, we use the daily social media activities of 56 major airlines on Twitter around the time of the Germanwings Flight 9525 crash to study how nonfocal airlines ran offensive and defensive marketing on social media before and after the crisis. We find that, on average, nonfocal airlines increased their defensive marketing efforts but decreased their offensive marketing efforts after the crash, which we attribute to the negative spillover effect. However, the strategic adjustment of decreasing offensive marketing is attenuated by the competition between nonfocal airlines and the focal one, which we attribute to the moderating role of the competitive effect. These results are shown to be robust in various tests and reveal how the interplay of the two effects of a product-harm crisis on nonfocal firms shapes their postcrisis social media strategies. The online appendix is available at https://doi.org/10.1287/isre.2017.0707 .